Stress Analysis of the Rotating Carbon-Carbon Composite Disk of an Axial Compressor - Behrooz Shahriari; Keyvan Shojaei (Mechanics of Advanced Composite Structures)
The correct materials selection in the design of aerospace structures reduces the weight and increases structural efficiency. Since the rotor in gas turbine engines has a significant weight, it is important to reduce its weight. The rotating disks in these rotors are subjected to mechanical and thermal loads and experience high-temperature gradients and angular velocities. This work aims to analyze the stress of a rotating disk made of carbon-carbon (C/C) composite to withstand mechanical and thermal loads and reduce the weight of the rotor. The behavior of constant thickness C/C composite disks is studied based on the Tsai-Wu Failure Theory. To do so, first, the basic properties of the material, disk size, rotation speed, temperature distribution, and other requirements are determined. The differential governing equations are obtained by assuming the plane stress state, Hooke's law, and compatibility condition, and the stresses, strains, and displacements are obtained. Considering the safety factors of 1 and 1.5, the critical velocities are calculated using the Tsai-Wu failure theory. Finally, according to the information obtained from the analysis, the evaluation of disks with different layers is compared with other similar disks made with different materials.